Modulation of NR2B-regulated contextual fear in the hippocampus by the tissue plasminogen activator system - Norris, Erin H. (National Academy of Sciences, 2007)
Contextual fear conditioning is regulated by the hippocampus, and NR2B, a subunit of the NMDA receptor (NR), is involved in this process. We show that acute stress modulates tissue plasminogen activator (tPA) activity in the hippocampus by inducing expression of its inhibitor, plasminogen activator inhibitor-1. Acute stress increases NR2B expression and ERK1/2 phosphorylation, a classical marker of postsynaptic plasticity, in the hippocampus. tPA forms a complex with NR2B and is necessary for binding NR2B to postsynaptic density-95, allowing for NR activation and membrane anchoring. Acute stress increases the interaction between NR2B and RACK-1, which is also dependent on tPA, further suggesting that tPA is an important factor in NMDA signaling and plasticity in the hippocampus. Finally, acutely stressed tPA(−/−) mice show a decrease in contextual fear conditioning compared with stressed WT mice. These results indicate that tPA is a key modulator in stabilizing the NR complex during stress and participates in changes in behavior and synaptic plasticity.